219k views
3 votes
Solve the equation

3(n+11)-5n = -2(n-12)+9

User SakisTsalk
by
4.4k points

2 Answers

7 votes

Answer:

infinite number of solutions

Explanation:

3(n + 11) - 5n = - 2(n - 12) + 9 ← distribute parenthesis on both sides

3n + 33 - 5n = - 2n + 24 + 9 , that is

- 2n + 33 = - 2n + 33

since the expressions on both sides are the same then any value of n will make the equation true.

thus the equation has an infinite number of solutions

User Ysakamoto
by
5.7k points
4 votes

Answer:

Any real value. Infinite no. of solutions.

Explanation:

Let's open the bracket first. Multiply the term outside the bracket with each term inside the bracket.


\Rightarrow 3(n+11)-5n = -2(n-12)+9


\Rightarrow 3n + 33 - 5n = -2n + 24 + 9

Now simplify the n terms on both sides


\Rightarrow -2n + 33 = -2n + 33

Here both LHS and RHS are same. And the terms gets canceled. Any real value of n satisfy the above equation.

User Jpmc
by
4.6k points